Status Mutu Air Sungai Unda Pada Lahan Eks Galian C Kabupaten Klungkung - I Made Sara Wijana; Abd. Rahman As-syakur; Made MS Mahendra; I GA Kunti Sri Panca Dewi (Environmental Research Center (PPLH) of Udayana University, 2020)
The Unda River (Tukad) is the second largest river in Bali Province after the Ayung River. The Unda River has been used for various activities, such as tourism activities for white water rafting and agricultural irrigation activities. In addition, Unda River water is planned to be used as a raw water source in the planned construction of the Bali Cultural Center (PKB) which is planned to be built in the lower reaches of the Unda River. Therefore, it is necessary to conduct research related to the water quality of the Unda River, especially in the Lower Unda River. Water quality analysis refers to class II water quality standards according to the Bali Governor Regulation Number 16 of 2016. Meanwhile, the analysis of water quality status uses the pollution index (IP) according to the Decree of the Minister of the Environment Number 115 of 2003. The results of the analysis show that water quality parameters that exceed the highest quality standard is downstream (sampling point 3) with 4 (four) parameters, namely Total Dissolved Solid (TDS), chemical oxygen demand (COD), total coliform and fecal coli. While the sampling points 1 (one) and 2 (two), the parameters that exceed the quality standard are total coliform and fecal coli. In addition, the results of this study also show that the pollution index value downstream is increasing, where at sampling point 1 which is a DAM location has a pollutant index of 3.78 (light pollution) and at sampling point 2 of 6.27 (moderate pollution) and at sampling point 3 of 7.67 (medium polluted).